Association of Lubricants, Foreplay, and Communication with Lower Dyspareunia Pain among Perimenopausal Women - Karwati Karwati; Damai Yanti; Sri Maryati; Rochmawati Rochmawati (UPT Publikasi Ilmiah Universitas Islam Bandung, 2026)
Dyspareunia, or pain during sexual intercourse, is common among perimenopausal women, negatively affecting their quality of life, sexual satisfaction, and relationships. Limited observational data exists on non-pharmacological self-management strategies for pain relief, particularly in Indonesia. This study examines the associations between three self-management strategies—vaginal lubricants, enhanced foreplay, and couple communication—and the reduction of dyspareunia pain in Indonesian perimenopausal women. A cross-sectional study involving 63 women (aged 40–55) with dyspareunia who had used at least one self-management strategy for at least four weeks was conducted at Puskesmas Cimahi Utara, Cimahi, Indonesia, from January 2024 to June 2024. Participants were divided into four groups: lubricants (n=14), foreplay (n=30), communication (n=8), and combined approaches (n=11). Pain intensity was assessed using the Numerical Pain Rating Scale (NPRS). Pre-strategy scores were obtained retrospectively, and post-strategy scores reflected current pain levels. Welch ANOVA and Games-Howell post-hoc tests analyzed mean pain reduction across groups. Significant differences in pain reduction were found among the groups (F(3.59)=24.36, p<0.001, η2=0.553). Lubricants showed the greatest reduction in pain (mean=1.86±0.95 points; 95% CI=1.30–2.41), significantly more than communication (p=0.0295, Cohen's d=0.68) and approaching significance compared to foreplay (p=0.0542, Cohen's d=0.68). All groups reported statistically significant pain reductions. In conclusion, vaginal lubricant use led to the greatest reduction in self-management strategies for dyspareunia pain among perimenopausal women in Indonesia, outperforming enhanced and foreplay couple communication strategies.